Pap Smear Practices among Female Healthcare Professionals in Indonesia and Their Associated Factors - Ramli, Richelle; Angelina (Fakultas Kedokteran Universitas Pelita Harapan, 2024)
Introduction : Cervical cancer is the fourth most frequent disease in women worldwide. However, pap smear coverage in Indonesia remains below the target. The purpose of this study was to describe pap smear practice among female healthcare professionals and its associated factors. Methods : This cross-sectional study was conducted from August 2022 to June 2023 among married female healthcare professionals of reproductive age who worked in Kelapa Dua district, Tangerang, Banten, Indonesia. Three general hospitals, two primary clinics, and one community health center were involved in this study. Data was collected using a self-administered questionnaire and analyzed using a chi-square test. Results : From 236 respondents, only 80 respondents (33.9%) had pap smear tests. The most common reasons for not doing the test were lack of time and having not experienced any of the symptoms. Those who were doing the pap smear tests were likely to be more than 40 years old (OR 29.900; 95% CI 9.595 – 93.172; p<0.001), married for more than 10 years (OR 28.737; 95% CI 9.955 – 82.955; p<0.001), multiparous (OR 6.941; 95% CI 2.706 – 17.805; p<0.001), and have higher economic income (OR 7.333; 95% CI 1.443 – 37.274; p=0.020). Female healthcare professionals other than medical practitioners, nurses, or midwives were less likely to do the pap smear tests (OR 0.370; 95% CI 0.167 – 0.823; p=0.02). Conclusion: Pap smear practice among female healthcare professionals in Indonesia was inadequate. Age, marriage duration, parity status, types of healthcare professionals, and socioeconomic status were significantly associated with pap smear practice.